River Deltas Research Recent Advances - Manning, Andrew J. (IntechOpen, 2022)
River deltas are among the most sensitive and widely exploited territories habitats on Earth. Although predominantly shallow aquatic environments, river deltas are extremely important environments socioeconomically and their usage places ever-increasing stresses on these habitats, especially where there is any anthropogenic involvement. The effective governance and administration of river delta regions often requires an intricate scientific understanding of the various contributary natural processes. River Deltas Research - Recent Advances is a book that draws on the most recent world-class scientific research on river delta topics including climate change, water quality, geomorphology, anthropogenic stresses, water quality, sedimentation, ecosystems, and many more. The research was carried out by researchers who specialise in the river deltas and related issues.